Planetary ball‐milling of AlON powder for highly transparent ceramics. Issue 5 (23rd October 2018) - Feng, Zhao; Qi, Jianqi; Huang, Xu; Guo, Xiaofeng; Yu, Yin; Cao, Xiuxia; Wang, Yuezhong; Wu, Di; Meng, Chuanmin; Lu, Tiecheng
Abstract: A detailed investigation of planetary ball‐milling for coarsened AlON powder was carried out. Our results showed that the weight ratios of milling ball‐to‐powder, the revolution rate and the planetary ball‐milling time have significant impacts on the microscopic morphology, particle size distribution and average particle size of powder. The process and mechanism were analyzed, and the outcome of our study can be used to optimize the complicated planetary ball‐milling method by controlling the planetary ball‐milling time or adjusting the revolution rate at the final stage of planetary ball‐milling. Sequentially, using fine and uniform AlON powder by optimized planetary ball‐milling with an average particle size below 300 nm and excellent sintering properties, highly transparent AlON ceramic with an in‐line transmittance of 84% at 2000 nm was successfully prepared through pressureless sintering at 1880°C for 6 hours using the elaborative treated powder synthesized from carbothermal nitridation method.